A relationship between perceived organizational support and percieved supervisor support towards work engagement among employees at MARA Professional Colleges, Malacca. / Mohammad Nazaruddin Marso @ Samiran - Marso @ Samiran, Mohammad Nazaruddin (Faculty of Business and Management, 2017)
This study aims to investigate the roles of perceived organizational support (POS) and perceived supervisor support (PSS) towards work engagement. Four objectives have been determined in order to achieve the purpose of this study. First, to identify the level of work engagement among employees in MARA Professional Colleges in Malacca. Second, to investigate the relationship between POS and work engagement. Third, to investigate the relationship between PSS and work engagement. Fourth, to investigate the factor that gives most influence on work engagement in MARA Professional Colleges in Malacca. The population of the study consists of 180 employees, whilst the sample consists of 123 respondents from 3 departments, namely; the management team, administrative unit and academic unit. The data were collected by distributing 150 questionnaires, and 123 returned questionnaires were used in the study. To analyse the data, descriptive, correlation, and regression analyses were used. The results of the study showed that there were moderate level of work engagement in the organization. From the correlation analysis conducted, the results revealed that there are significant and moderate relationships between POS and work engagement; and PSS and work engagement. Meanwhile, from regression analysis conducted, it was found that POS gave more influence to work engagement, than PSS. Last but not least, from the Model Summary derived from the analysis, it showed that POS and PSS only influence work engagement by 29.8%, and another 70.2% was influenced by other factors. In a nutshell, POS and PSS do give influence over work engagement, but in a small scale.